'Reverse-Engineering' of a Results Framework for Monitoring and Evaluation – The Case of Punjab Vocational Training Council. Issue 2 (September 2019) - Bashir, Mohsin
Several government and non-profit organizations in Pakistan are currently going through a transition towards performance management systems that are based on internationally accepted monitoring and evaluation (M&E) frameworks. More often than not, these transitions are driven by requirements of donor organizations. While it is fairly uncomplicated and helpful to develop an M&E framework before the initiation of a programme, organizations find it quite tricky to develop such a system while the operations are already underway. This case presents the story of a public sector organization that created an M&E team that was able to successfully reverse-engineer its operations into an M&E framework. It can, therefore, prove to be a very helpful resource for managers and consultants attempting to develop M&E frameworks for ongoing programmes. Findings and analysis are presented in such a way that the case bears the appearance of a step-by-step guideline. While the case is focussed around developing a results framework, the learning can easily be generalized to other platforms, specifically the logical framework approach. Data for this case was collected during a 6-month-long consulting assignment. Data sources include interviews with the employees, internal organizational documents as well as published reports and statistics.